Предмет: Алгебра,
автор: korolek1803
Решением уравнения является (х+4)^2-(х-3)^2=14х+5 является?
Приложения:
Ответы
Автор ответа:
0
(х+4)^2-(х-3)^2=14х+5
х²+8х+16-х²+6х-9=14х+5
14х+7=14х+5
14х-14х= -2
ответ: х-это любое число
х²+8х+16-х²+6х-9=14х+5
14х+7=14х+5
14х-14х= -2
ответ: х-это любое число
Похожие вопросы
Предмет: Қазақ тiлi,
автор: esenbaevserik77
Предмет: Английский язык,
автор: Miа16
Предмет: Геометрия,
автор: kalmykova201510
Предмет: Математика,
автор: Popovic1998
Предмет: Алгебра,
автор: CobiPlus